Level of carbon dioxide diffuse degassing from the ground of Vesuvio: comparison between extensive surveys and inferences on the gas source - Domenico Granieri; Maria Luisa Carapezza; Rosario Avino; Stefano Caliro; Carlo Cardellini; Giovanni Chiodini; Marco Donnini; Carmine Minopoli; Massimo Ranaldi; Tullio Ricci; Luca Tarchini (Annals of Geophysics, 2013)
An extensive campaign of diffuse CO2 soil flux was carried out at the cone of Vesuvio in October 2006 with two main objectives: 1) to provide an estimation of CO2 diffusely discharged through the soils in the summit area and 2) to evidence those sectors of the volcano where structural and morphological conditions could favour the gas output. The survey consisted of 502 measurements of soil CO2 flux homogenously distributed over an area of about 1.8 km2. Results of this survey were compared with those obtained during a similar campaign carried out by Frondini et al. in 2000, from which we have taken and reinterpreted a subset of data belonging to the common investigated area. Graphical statistical analysis showed three overlapping populations in both surveys, evidencing the contribution of three different sources feeding the soil CO2 degassing process. The overall CO2 emission pattern of 2006 is coherent with that observed in 2000 and suggests that a value between 120 and 140 t/day of CO2 is representative of the total CO2 discharged by diffuse degassing from the summit area of Vesuvio. The preferential exhaling area lies in the inner crater, whose contribution resulted in 45.3% of the total CO2 emission in 2006 (with 62.8 t/day) and in 57.4% (with 70.3 t/day) in 2000, although its extension is only 13% of the investigated area. This highly emissive area correlated closely with the structural discontinuities of Vesuvio cone, mainly suggesting that the NW-SE trending tectonic line is actually an active fault leaking deep gas to the bottom of the crater. The drainage action of the fault could be enhanced by the “aspiration” effect of the volcanic conduit.